Былины: книга для внеклассного чтения. 5-7 классы - Круглов Ю. Г. (Просвещение, 1986)
Экземпляры: БС (20170731) / Инвентарный номер: РТШ47000 / Сис.шифр: 82.3(0) / Авт.знак: Б 95 / ГРНТИ: 17.71 / ББК: 82.3(2=411.2)-441.06